2022
DOI: 10.3390/jcm11061742
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Presentation of the Multisystem Inflammatory Syndrome in Children: Data from a Cluster Analysis

Abstract: Background: The aim of this study was to evaluate the outcomes of patients with the multisystem inflammatory syndrome in children (MIS-C) according to phenotypes of disease and define the prognostic factors for the severe course. Methods: This cross-sectional study included 293 patients with MIS-C from seven pediatric rheumatology centers. A two-step cluster analysis was performed to define the spectrum of disease and their outcomes were compared between each group. Results: Four subgroups were identified as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“…Since inflammatory cells such as neutrophils and lymphocytes play an important role in the pathogenesis of MIS‐C, it seems reasonable to focus on NLR. Sönmez et al found higher NLR in patients with a severe disease course in a multicenter study that included 293 MIS‐C patients 41 . Our study determined that NLR was effective in predicting disease severity, admission to hospital, need for intensive care, and anakinra treatment in MIS‐C patients.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Since inflammatory cells such as neutrophils and lymphocytes play an important role in the pathogenesis of MIS‐C, it seems reasonable to focus on NLR. Sönmez et al found higher NLR in patients with a severe disease course in a multicenter study that included 293 MIS‐C patients 41 . Our study determined that NLR was effective in predicting disease severity, admission to hospital, need for intensive care, and anakinra treatment in MIS‐C patients.…”
Section: Discussionmentioning
confidence: 48%
“…Sönmez et al found higher NLR in patients with a severe disease course in a multicenter study that included 293 MIS-C patients. 41 Our study determined that NLR was effective in predicting disease severity, admission to hospital, need for intensive care, and anakinra treatment in MIS-C patients. The sensitivity of NLR in predicting disease severity and specificity was 83.6% and 81.4%, respectively.…”
Section: Discussionmentioning
confidence: 82%
“…Sixty-seven (54.5%) patients were followed up in the intensive care unit (ICU). According to studies from Turkey, the rate of intensive care hospitalization was 29.6-46.7%, the need for mechanical ventilation was 11.1-12.4%, and the need for vasoactive drug support was 17.7-35.7% [20][21][22][23][24]. In the review of [15].…”
Section: Discussionmentioning
confidence: 99%
“…Over half of children with MIS-C present to the intensive care unit (ICU) 4-6 weeks after initial SARS-CoV-2 infection (Cui et al, 2021; Patel, 2022; Vogel et al, 2021). Hallmark symptoms of MIS-C include a prolonged high fever, rash, gastrointestinal symptoms, cardiovascular dysfunction, and signs of inflammation (Feldstein et al, 2020; Hoste et al, 2021; Sönmez et al, 2022; Whittaker et al, 2020). Early recognition and treatment of MIS-C are essential to prevent serious complication and death.…”
Section: Introductionmentioning
confidence: 99%